THE STATE POLICY PRINCIPLES OF THE CONFLICT-AFFECTED TERRITORIES RECOVERY - Balueva O.V.; Kelembet O.S. (Pressing Problems of Public Administration, 2017)
The article is dedicated to the formation of the state policy of the territories recovery that was damageddue to the con ict in the East of Ukraine. Social-economic situation, which formed in the temporaryoccupied territories, was analyzed. The basic principles, which it is suggested to form and implementthe state policy of the con ict-affected areas recovery, are highlighted. Methods that need to be usedin the ful llment of the state policy of the con ict-affected areas recovery are analyzed.